Application of System and Synergetic Paradigm of Management of Social-Economic, Educational Processes in Ukraine - Alexander Voznyuk; Larysa Zdanevych (Pedagogical Discourse, 2019)
Due to widening the system and synergetic methodology in the sphere of socio-economic research, the synergetic methodology is extrapolated on managing social-economic processes at the level of constructing the model of such a process. The research is consecutively conducted on three methodological levels – the general/overall (general principles of synergetics are realized in socio-economic sphere), the peculiar/specific (general principles of synergetics are realized in socio-economic systems management) and the single/individual (the synergetic principles of socio-economic systems management are realized in the sphere of education on the level of the model of educational systems management using temporary self-ruled managerial target teams). It is stated that the system-synergetic view of the world reveals certain fundamental aspects of the behavior of natural and socio-economic systems in the context of their control and governance. It is shown that the use of temporary self-ruled managerial target teams, being the major element of a synergetic model of socio-economic management, is realized according to synergetic principles and processes.The use of temporary self-ruled managerial target team is realized according to synergetic principles and processes due to which we gain synergetic effect consisting in emerging and system (cooperative) phenomena. The teams are created quite spontaneously due to new educational (social) problems thus quickly reacting at outer environment’s disturbances. In this way, the teams can be considered to be open (dissipated) self-determined systems. The management capacity of the teams stems from their flexibility, multi-targeted nature and staff complexity since the members of the teams are recruited from various strata of society. Due to complexity and diversity of the teams they can react at different social fluctuations including the weakest signals of social-economic environment. The teams are quite self-determined and creative units since their temporary staff is recruited from different socio-economic establishments; so the teams’ members are not strictly fixed and are not materially dependant on team’s activities which gain creative character: one of the major characteristics of creative activities is connected with non-pragmatic orientation of the person involved in creativity thus revealing non-adaptive modus of a creative artist working according to the principle «the art for the sake of the art»).